Zionism in Sweden - Narrowe, Morton (Nordisk judaistik/Scandinavian Jewish Studies, 1981)
The first Zionist Congresses left the Jewish majority in Sweden relatively untouched. It is true that Professor Gottlieb Klein, the influential Rabbi of Stockholm, a student and personal friend of the great German reformer, Abraham Geiger, and to a lesser extent his colleague in Gothenburg, Dr. Koch, did oppose the Jewish national movement, but not until January 1910, when the first Zionist society was founded in Stockholm, did Swedish Jews seriously consider this alternative to their “prophetic” Judaism. Efforts by the Zionists in Sweden to gain public attention for themselves were mainly ineffectual until Kurt Blumenfeld, the General Secretary and Chief of Information for the World Zionist Organization in Berlin, visited Stockholm and Gothenburg in 1912 to deliver several open lectures.